2019
DOI: 10.1161/circep.119.007663
|View full text |Cite
|
Sign up to set email alerts
|

Arrhythmia Mechanisms and Outcomes of Ablation in Pediatric Patients With Congenital Heart Disease

Abstract: Background: In contrast to the adult population with congenital heart disease (CHD), arrhythmia mechanisms and outcomes of ablation in pediatric patients with CHD in recent era have not been studied in detail. Aims of this study were to determine arrhythmia mechanisms and to evaluate procedural and long-term outcomes in pediatric patients with CHD undergoing catheter ablation. Methods: Consecutive patients <18 years of age with CHD undergoing cathete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 36 publications
1
17
0
Order By: Relevance
“…Because of early diagnosis and early surgery, the prognosis of patients with CHD has greatly improved in recent decades. However, the ameliorated survival rate is accompanied by an increase in arrhythmia morbidity (35), especially MAT, which is related to a specific type of CHD, palliative surgery, and radical surgical repair (36)(37)(38). Another study demonstrated that 50% of Klippel-Feil syndrome, tetralogy of Fallot, Noonan syndrome, myocarditis, familial hypertrophic obstructive cardiomyopathy, RASopathy syndrome, and Heterotaxy syndrome have a cardiac anatomic abnormality, which facilitates the development of MAT (3,5).…”
Section: Congenital Heart Disease and Cardiac Anatomic Abnormalitymentioning
confidence: 99%
“…Because of early diagnosis and early surgery, the prognosis of patients with CHD has greatly improved in recent decades. However, the ameliorated survival rate is accompanied by an increase in arrhythmia morbidity (35), especially MAT, which is related to a specific type of CHD, palliative surgery, and radical surgical repair (36)(37)(38). Another study demonstrated that 50% of Klippel-Feil syndrome, tetralogy of Fallot, Noonan syndrome, myocarditis, familial hypertrophic obstructive cardiomyopathy, RASopathy syndrome, and Heterotaxy syndrome have a cardiac anatomic abnormality, which facilitates the development of MAT (3,5).…”
Section: Congenital Heart Disease and Cardiac Anatomic Abnormalitymentioning
confidence: 99%
“…The CHD patients might have increased VT burden due to surgical scar and hemodynamic abnormalities before or after surgery [12,13]. However, the acute long-term procedural success rate in the CHD patients in this series was good and VT did not recur in all patients during follow-up after last procedure.…”
Section: Discussionmentioning
confidence: 63%
“…Data on TR-associated ventricular arrhythmia are very scarce, focused on Ebstein anomaly. This congenital heart disease can be associated with single or multiple right-sided accessory pathways or Mahaim pathway generating reentrant atrioventricular tachycardia and the risk of life-threatening VA depending of the electrophysiological properties of accessory pathway ( 127 ). Ablation of these arrhythmias can be performed safely in pediatric patients ( 127 ).…”
Section: Tricuspid Regurgitationmentioning
confidence: 99%
“…This congenital heart disease can be associated with single or multiple right-sided accessory pathways or Mahaim pathway generating reentrant atrioventricular tachycardia and the risk of life-threatening VA depending of the electrophysiological properties of accessory pathway ( 127 ). Ablation of these arrhythmias can be performed safely in pediatric patients ( 127 ). Other types of congenital heart disease, with right heart volume overload such as atrial septal defect and repaired tetralogy of Fallot may also lead to VAs ( 128 ).…”
Section: Tricuspid Regurgitationmentioning
confidence: 99%